Encouraging active transportation to school: Lessons learned from implementing a walking school bus program in Northeastern Ontario. (December 2020) - Scharoun Benson, S.M.; Bruner, B.; Mayer, A.
Abstract: Introduction: Few Canadian children meet physical activity guidelines. Active transportation to school may be a way to increase physical activity and walking school buses have shown promise; yet, few studies consider Northern settings. Methods: Experiences of individuals and factors related to implementation of a walking school bus pilot in Northeastern Ontario were explored using semi-structured interviews (parents), and focus groups (students and conductors). Data were audio-recorded, transcribed verbatim, and categorized using thematic analyses. Results: Six themes emerged from the data: (1) Health and Social Benefits; (2) Learning Safety Skills; (3) Participant Satisfaction; (4) Environmental Factors; (5) Implementation Challenges; and (6) Moving Forward. Taken together, an increase in physical activity, socializing and community participation, being outdoors, benefits to mental health, knowledge of road safety, and perceptions of environmental influences were revealed as positive outcomes. Although conductors and students were worried about distance, parents perceived the distance as acceptable. Despite initial challenges, participants generally agreed the pilot was well organized. University student volunteers played a large role in success. Conclusions: In Northeastern environments, opportunities for active transportation to school and physical activity are influenced by many factors. Sustained initiatives are needed to improve upon the determinants of active transportation to school at the various ecological levels where they can be most effectively targeted. Highlights: Experiences with a pilot walking school bus in Northeastern Ontario were explored. Positive outcomes included increased physical activity and being outdoors. Socializing, community involvement, and mental health benefits were also revealed. Road safety, and perceptions of environmental impact were also positive benefits. Sustained initiatives are needed to improve active transportation to school.